نشوء الحكم القبلي في العراق واثرهُ في تصفية القوى القومية ونهاية حكم عبد السلام عارف 1964-1966م - عاتي طالب هاشم عاتي; أ. د رحيم كاظم محمد الهاشمي (Journal of College of Education, 2023)
Abd al-Salam Aref, after seizing power by excluding the Baathists in the November 18,1963 coup, worked to change his ideology, in which he stressed the need for the army, with its various orientations, to control the reins of government by adopting it. A kinship system for his clan to maintain his power, and as a reflection of this, the tribal system began to emerge after the liquidation of most of the national elements opposed to his rule in light of their exclusion from their positions or their deportation outside the country. country and replacing them with elements close to it from the people of his clan and city, on whom he relied to achieve this goal, and as a result the political system became led by one tribe throughout his reign